Implementation of Presidential Regulation Number 12 of 2021 Concerning Government Procurement of Goods and Services in the City of Banjarmasin - Irawanto; Semuel Risal; Moh. Heru Budihantho; Dedy Sadikin (International Journal of Sustainability in Research, 2023)
The title of this research is which aims to determine the description, supporting, and inhibiting factors as well as providing solutions faced in the Implementation of Presidential Regulation Number 12 of 2021 concerning the Procurement of Government Goods and Services in the City of Banjarmasin. His study uses qualitative research. The selection of information is carried out by purposive sampling, where researchers prefer to choose informants who meet certain criteria and are considered to know about what researchers expect and can be trusted with the accuracy of the information and know the problems in depth at the time of the interview. The results of this study indicate that the communication factors, resources, disposition, and approach to the implementation of Government Policy Number 12 of 2021 concerning Banjarmasin Goods and Services have not been realised optimally so that Presidential Regulation Number 12 of 2021 Procurement of goods and services has not run optimally. Factors in implementing the policy of Presidential Regulation Number 12 of 2021, namely the existence of Regional Regulations or other forms of regulations that exist at the local level as well as support for facilities and infrastructure including the availability of an operational budget determined through the APBD. On the external side, the DPRD's attention to efforts to implement the Presidential Regulation Number 12 of 2021 is very low.